A study on the factor that contribute to group hospital & surgical insurance claim denial / Suraya Salehuddin - Salehuddin, Suraya (2010)
Hospital & Surgical Insurance is one of product provided by all of insurance company in the world. Nowadays people are becoming aware on the importance of having Hospital & Surgical Insurance. There are several factors that influence people to buy Hospital & Surgical Insurance. One of the major factors is increasing in medical cost. Best treatment needs high expenses especially critical disease because it involves high technology in medical care and treatment and these technologies have help people to live longer. Nowadays the populations of senior citizens have been increased. Table 1.1 below is showing the increasing in populations of senior citizens in Malaysia.Senior citizens need more medical care than younger population and it causes the increasing in medical expenses. Besides that the poor lifestyle of individual such as bad eating habits, smoking, lack of exercise and drug and alcohol abuse has made people always seek for medical treatment. Hospital & Surgical Insurance can help people to reduce the medical costs as it provides the reimbursement for all or part of hospital bills and protects the insured from high medical costs. So, by having Hospital & Surgical Insurance people would not worry for paying all medical expenses as long as it states in policy, insurance company will provide coverage for claimant. Additionally people can go to the doctor anytime when feeling bad and as a result they will have better chance of staying healthy. Insurance company also provide Group Hospital & Surgical Insurance (GHSI). This research will be focus on GHSI. It provides protection for their employee to avoid employees from financial losses. Some employers may provide only basic plan which is coverage for employee itself only, while others may provide coverage for employee’s family members. It insures the employee or dependant if they are admitted to a hospital whether caused by illness or accidental injury.